Jedrski procesi v zvezdah - Gospodarič, Jan (Matrika, 2014)
The article includes a description of nuclear reactions in stars and how and under what conditions these processes take place. The evolution of stars is concise associated with reactions in their interior. The article also focused on the frequency of occurrence of elements in the universe and the reasons for their occurrence. Also discussed are the elements which are not the result of fusion of nuclei, but capture of neutrons.
Keywords: capture of neutrons; evolucija zvezd; jedrska fuzija; jedrske reakcije; nuclear fusion; nuclear reactions; star evolution; stars; zajem nevtronov; zvezde